Assessment of Bite Force and Masseter and Temporal Muscles Thickness in Adult Women Undergoing Buccal Fat Pad Removal Surgery–Bichectomy - Branco, Thamyres; Palinkas, Marcelo; Cardoso, Alice Helena de Lima Santos; Bettiol, Nicole Barbosa; de Vasconcelos, Paulo Batista; Silva, Gabriella Simi Gariba; Chiaratto, Jéssica Brandani; de Lima, Patricia Santos; Xavier, Samuel Porfírio; Regalo, Isabela Hallak; Siéssere, Selma; Regalo, Simone Cecilio Hallak (UI Scholars Hub, 2024)
Objective: Bichectomy, a surgical procedure that removes the buccal fat pad, can affect masticatory function, including bite force and muscle thickness, in adult women. This study aimed to assess the bite force as well as masseter and temporal muscle thicknesses before and 30 and 60 days after bichectomy in adult women. Methods: This longitudinal study included a sample of 20 adult women (mean age 31.1 ± 9.84 years), with normal occlusion and no history of temporomandibular disorder. The molar bite force was assessed using a dynamometer, while the masseter and temporal muscle thicknesses at rest and during dental clenching were evaluated using an ultrasound device. Data were analyzed using repeated-measures analysis of variance with Bonferroni correction (p < 0.05). Results: Significant differences were noted between periods in both right (p = 0.01) and left molar bite forces (p = 0.05). The right molar bite force decreased 30 days after buccal fat pad removal surgery and increased after 60 days. Conversely, a decline in the left molar bite force was observed during the postsurgical period. No significant differences were detected in masticatory muscle thickness. Conclusion: Buccal fat pad removal surgery affects molar bite force but does not significantly alter masticatory muscle thickness.